Clinical Features of Systemic Sclerosis–Mixed Connective Tissue Disease and Systemic Sclerosis Overlap Syndromes. Issue 5 (3rd April 2021) - Fairley, Jessica L.; Hansen, Dylan; Proudman, Susanna; Sahhar, Joanne; Ngian, Gene‐Siew; Walker, Jenny; Strickland, Gemma; Wilson, Michelle; Morrisroe, Kathleen; Ferdowsi, Nava; Major, Gabor; Roddy, Janet; et al.
Abstract : Objective: To describe the clinical characteristics and outcomes of systemic sclerosis–mixed connective tissue disease (SSc–MCTD) and SSc overlap syndrome. Methods: We included patients from the Australian Scleroderma Cohort Study who met American College of Rheumatology/European Alliance of Associations for Rheumatology criteria for SSc. Three mutually exclusive groups were created: SSc–MCTD, SSc overlap, and SSc only. Univariate comparison of clinical features was performed by analysis of variance or chi‐square test. Survival analysis was performed using Kaplan‐Meier (KM) curves and Cox proportional hazards regression models. Results: Of 1, 728 patients, 97 (5.6%) had SSc–MCTD, and 126 (7.3%) had SSc overlap. Those with MCTD–SSc were more commonly Asian (18.3% versus 10.1% in SSc overlap, and 3.6% in SSc only; P < 0.0001) and younger at disease onset (38.4 years versus 46.5 or 46.8 years, P < 0.0001). Those with SSc–MCTD or SSc overlap were more likely to have limited cutaneous SSc. All 3 groups had similar frequency of interstitial lung disease (ILD), although pulmonary arterial hypertension (PAH) was less common in SSc overlap. Synovitis and myositis were more common in SSc overlap and SSc–MCTD than in SSc only. KM curves showed better survival in SSc–MCTD than SSc overlap or SSc only ( P = 0.011), but this was not significant after adjustment for sex and age at disease onset. SSc‐specific antibodies were survival prognostic markers, with antinuclear antibody centromere or anti‐RNP conferring better survival than anti–Scl‐70 or anti–RNA polymerase III ( P = 0.005). Patients with SSc–MCTD and SSc overlap had lower mortality following diagnosis of ILD and PAH than patients with SSc only. Conclusion: This study provides insights into the clinical characteristics of patients with SSc–MCTD, SSc overlap, and SSc only and shows that anti‐RNP antibodies are associated with better survival than anti–Scl‐70 and anti‐RNA polymerase III antibodies.